TRANSITION OF GENDER RELATIONS IN THE MANDAILING BATAK COMMUNITY: BETWEEN PATRIARCHAL CULTURE, PATRILINEAL SYSTEM, AND SOCIAL CHANGE IN EAST SAMBIREJO VILLAGE, PERCUT SEI TUAN DISTRICT, DELI SERDANG REGENCY (International Journal of Cultural and Social Science, 2026)
The Batak Mandailing community adheres to a patrilineal system and patriarchal culture that still affects gender relations, but social changes have encouraged a shift in the role of women in people's lives. This study aims to analyze public perception of gender equality, its implementation in daily life, and the factors that affect its implementation in East Sambirejo Village, Percut Sei Tuan District. The study uses a descriptive qualitative approach with data collection techniques through semi-structured interviews, observations, and documentation of purposively selected informants. Data is analyzed through data reduction, data presentation, and conclusion drawn. The results of the study show that society is starting to have a more open view of gender equality, especially in the fields of education, economics, and women's social participation. However, patriarchal culture and the patrilineal system still influence the division of family roles, decision-making, and the position of women in indigenous life. Driving factors include education, economic conditions, multi-ethnic social environment, and the development of the times, while inhibiting factors include patriarchal culture, patrilineal systems, male dominance in customs, and women's dual workload. This study concludes that the Batak Mandailing community is in a transition phase towards more equal gender relations, although it is still limited by patriarchal culture and patrilineal systems.